If content is king, conversion is queen: The dilemma of Dona Diva - Isadora Mara da Silva; Jailson Lana; Raul Beal Partyka (Regepe Entrepreneurship and Small Business Journal, 2025)
This work presents the real story of Dona Diva, a semi-jewelry company operating in e-commerce and serving the entire national territory, both in wholesale and retail. This study focuses on highlighting the digital marketing strategies implemented by the company's founders and its marketing and sales team. Within this context, the primary objective is to investigate the importance of digital marketing and social media in showcasing the advantages and disadvantages (especially when misapplied) of these marketing and communication channels between the company and its customers. The central dilemma of the case is: *How can content be created for two distinct channels, with different characteristics and interests (B2B and B2C), to drive e-commerce sales for both?* The case was built using primary sources, through interviews with the company's founders, as well as secondary sources. The names of the founders, the company, and the originality of the story were faithfully preserved throughout.